Urine Vancomycin Level as a Method for Drug Monitoring in Patients With Normal and Decreased Kidney Function (Iranian Journal of Kidney Diseases, 2017)
Introduction. Therapeutic drug monitoring of vancomycin is an important issue in clinical decision-making and dosage modifying, particularly among patients in critical conditions and decreased kidney function. Urine is typically readily available in hospitalized patients and therapeutic drug monitoring in urine may be a reliable and noninvasive procedure compared to frequent blood sampling. We aimed to determine and validate the diagnostic yield of vancomycin trough level in urine. Materials and Methods. In a prospective study, 95 patients who were treated with vancomycin for any clinical condition were enrolled in this study. Patients were divided into 2 groups according to their glomerular filtration rate (greater than 80 mL/min/1.73 m2 versus 15 mL/min/1.73 m2 to 80 mL/min/1.73 m2). Vancomycin serum trough levels and simultaneous urine trough levels were detected by high-pressure liquid chromatography. Results. The mean serum and urine trough levels of vancomycin were 13.13 ± 1.34 mg/L and 7.79 ± 1.23 mg/L, respectively. The serum and urine trough levels had a positive linear correlation (r = 0.38, P < .001), which was also significant in patients with normal kidney function (r = 0.43, P = .001). The estimated serum concentration was equal to urine vancomycin concentration plus 5.3 mg/L. Conclusions. Urine levels of vancomycin correlate with simultaneous serum levels and may consistently predict serum levels in patients with normal kidney function. Therefore, urine vancomycin monitoring might be used as a noninvasive alternative to blood sampling, particularly in patients with normal kidney function.